Dissipative area-preserving one-dimensional Fermi accelerator model - Leonel, Edson D. [UNESP]; McClintock, P. V.E. (American Physical Society (APS), 2006)
The influence of dissipation on the simplified Fermi-Ulam accelerator model (SFUM) is investigated. The model is described in terms of a two-dimensional nonlinear mapping obtained from differential equations. It is shown that a dissipative SFUM possesses regions of phase space characterized by the property of area preservation. © 2006 The American Physical Society.